Physiological quality of ‘‘malagueta’’ and ‘‘biquinho’’ pepper seeds during ontogeny - Abud, Haynna Fernandes; Araujo, Eduardo Fontes; Araújo, Roberto Fontes; Araujo, Alisson Vinicius; Pinto, Cleide Maria Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work to evaluate the physiological changes during seed ontogeny of ‘‘malagueta’’ and ‘‘biquinho’’ pepper, and to determine the best stage for harvest. Flowers in anthesis were tagged daily, and fruits were collected at 25, 40, 55, 70, 85, and 100 days after anthesis (DAA). In each maturation time, seeds were evaluated for water content, dry weight, germination, first germination count, germination speed index, and accelerated aging. The beginning of seed development was characterized by dry matter accumulation, which occurred until 80 DAA for ‘‘malagueta’’ pepper and 70 DAA for ‘‘biquinho’’ pepper. In orthodox seeds, such as pepper, after reaching maximum dry matter, a decrease is observed in water content. At 100 DAA, water content was 14% for ‘‘malagueta’’ pepper and 15% for ‘‘biquinho’’ pepper. Seeds harvested at 25 and 40 DAA did not germinate. Germination percentage increased between 40 and 70 DAA, and decreased thereafter. Physiological maturity of ‘‘malagueta’’ and ‘‘biquinho’’ peppers occurs at approximately 70 DAA, which is the ideal time for harvest.